Implementation of Islamic Family Financial Planning Amidst the Covid-19 Pandemic - Lufthia Sevriana; Marizsa Herlina (International Journal of Entrepreneurship and Sustainability Studies, 2021)
Management of Muslim household finances contains several characteristics that distinguish it from non-Muslim household economic systems. In this study, the indicators are the knowledge of financial planning, experience of financial problems, knowledge of faith, and knowledge of Islamic financial instruments. The Respondents are married Muslims or Muslim individual who can manage Islamic family finances. The data were analyzed descriptively and continued with the SEM model estimation. The results showed that most respondents had not adjusted their financial budgets to the pandemic conditions. Meanwhile, from the SEM model, it is known that knowledge of financial planning, experience of financial problems, knowledge of Islamic financial instruments has an effect on Islamic financial planning with the greatest influence from knowledge of Islamic instruments of 0.48. The SEM Model of Islamic Family Financial Planning is a good enough model to describe the condition of respondents during the Covid-19 pandemic.